STABILIZATION OF THE ECOLOGICAL ENVIRONMENT (Web of Teachers: Inderscience Research, 2024)
In this regard, it is necessary to transport waste by hydraulic means in order to prevent long-term accumulation of waste in temporary waste collection places. This will allow the waste to be easily transported to special recycling landfills in a timely manner, and various sanitary diseases will be prevented. The main criterion of the article is to create a moral environment in the reception of consumer waste, to separate them according to the structure of the waste, and to reduce the labor force and achieve economic efficiency by using a hydraulic unit.